The Role Sharia Non-Bank Financial Institutions To Support SDGS Program - Trimulato Trimulato (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
AbstractPurpose - The purpose of this study is to describe the development of sharia IKNB and the role of Sharia IKNB to support SGDs.Method - The type of research used is qualitative with literature study. The analytical technique used is descriptive qualitative describing the development of Sharia IKNB, and the role of Sharia IKNB to support realization of the SDGs.Result - The results show the development of Sharia IKNB in the period from October 2020 to April 2021, Sharia Insurance assets grew by 6.26 percent, Pension Fund Institutions assets grew by 17.79 percent, Sharia Microfinance Institutions assets grew by 2.24 percent, Sharia Fintech Institutions assets grew by 85.54 percent. Meanwhile, Sharia Financing Institutions experienced a decrease in assets of -7.78 percent and Sharia Pawnshops experienced a decrease in assets of -6.95 percent. Certified halal products in 2021 grew by 2,531.49 percent.Implication - Sharia IKNB supports SDGs to achieve the goal of reducing hunger, sharia IKNB can support the real sector, and also has a social aspect. SDGs achieve prosperity in line with the Islamic economic function of income distribution.Originality - The research a more in-depth study of the role of Islamic finance in supporting the Sustainable Development Goals (SDGs) program. Researchers identify the role of Sharia Insurance, Sharia Financing Institutions, Pension Fund Institution, Sharia Pawnshop, Sharia Microfinance Institutions and Sharua Financial Technology.